Implementation of Duha Prayer in Enhancing Students' Spiritual Intelligence: A Case Study at Muhammadiyah High School (MAM) Bandung/Muhammadiyah Boarding School (MBS 1) Tulungagung - Fathur Rozi, M. Asep; Rahmawati, Atika Sovia (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2023)
The essence of education lies in instilling noble morals within students, fostering an environment free from humiliation. Recognizing the crucial need for children to internalize values, norms, and morals, this research explores the implementation of the Duha prayer at MA Muhammadiyah Bandung (MBS 1) Tulungagung. The institution's strategic adoption of a prayer program serves as a commendable initiative to cultivate a steadfast commitment to spirituality and personal development. This research focuses on three key aspects: the methodology employed in implementing the Duha prayer, identifying the supporting factors and obstacles encountered during the implementation of the Duha prayer; and assessing the impact of Duha prayer on the enhancement of spiritual intelligence among students. This research uses a qualitative approach, this descriptive research utilizes data collection methods such as interviews and documentation of observations. The data analysis involves three stages: data condensation, presentation, and conclusion. The validity of the data is ensured through triangulation techniques and multiple sources. The findings reveal a comprehensive understanding of the Duha prayer implementation at MA Muhammadiyah Bandung (MBS 1) Tulungagung, encompassing execution, supervision, guidance, and the purpose behind prayer implementation. Factors supporting the Duha prayer implementation include collaborative efforts between teachers and students, well-equipped prayer facilities, and a conducive environment. Challenges arise from the limited capacity of the mosque, necessitating a rotational approach and leading to tardiness among students. The impact of Duha prayer implementation manifests in students exhibiting heightened enthusiasm, steadfastness, honesty, and responsibility, contributing to an overall increase in spiritual intelligence.